Targeting KRAS: from metabolic regulation to cancer treatment - Yanyan Shi; Huiling Zheng; Tianzhen Wang; Shengpu Zhou; Shiqing Zhao; Mo Li; Baoshan Cao (Molecular Cancer)
Abstract The Kirsten rat sarcoma viral oncogene homolog (KRAS) protein plays a key pathogenic role in oncogenesis, cancer progression, and metastasis. Numerous studies have explored the role of metabolic alterations in KRAS-driven cancers, providing a scientific rationale for targeting metabolism in cancer treatment. The development of KRAS-specific inhibitors has also garnered considerable attention, partly due to the challenge of acquired treatment resistance. Here, we review the metabolic reprogramming of glucose, glutamine, and lipids regulated by oncogenic KRAS, with an emphasis on recent insights into the relationship between changes in metabolic mechanisms driven by KRAS mutant and related advances in targeted therapy. We also focus on advances in KRAS inhibitor discovery and related treatment strategies in colorectal, pancreatic, and non-small cell lung cancer, including current clinical trials. Therefore, this review provides an overview of the current understanding of metabolic mechanisms associated with KRAS mutation and related therapeutic strategies, aiming to facilitate the understanding of current challenges in KRAS-driven cancer and to support the investigation of therapeutic strategies.